Multiple Intelligences dalam Perspektif Al-Qur’an Surat An-Nahl Ayat 78 dan Relevansinya dengan Pendidikan Nasional - Marta Novika; Wedra Aprison; Hendrisab Hendrisab (Journal on Education, 2025)
Munif Chatib's Multiple Intelligences education concept places more emphasis on The Best Process, not The Best Input, where superior schools are schools that focus on the quality of the learning process, not on the quality of the students' input. The goal of becoming an educated or special child is to emphasize teacher creativity and expertise in applying it, we can do this in the world of learning between teachers and students. The research methodology of this study is literature, data obtained from books and scientific articles are collected and analyzed regarding the interpretation of the letter An-Nahal verse 78 and its relevance to the national education. The results of the discussion of this study state that whatever the name of the learning strategy that increases students' competence, the Multiple Intelligences theory will be a very broad container, able to accommodate all existing method and strategy terms. The theory of Multiple Intelligences is also very in accordance with the Quran Surah An-Nahl verse 78 which explains that humans are born in a state of not knowing anything, Allah gives hearing, sight and conscience so that humans develop in line with growth and learning in order to become insightful, intelligent and have noble character as is the aim of education. Its relevance to national education is very close because the national education goals emphasize multiple intelligences and is in line with the National Education System.